Islamic education: the philosophy, aim, and main features - Fatah Yasin, Raudlotul Firdaus; Shah Jani, Mohd. (2013)
Islam has put greater emphasis on the importance of acquisition and dissemination of knowledge (‘ilm) than any other human activities. In fact, it makes it compulsory (farḍ) upon its adherents, regardless of gender, to learn and disseminate knowledge. The obligation of seeking out knowledge is binding upon every Muslim by the command of the Qur’an and Sunnah of the Prophet (PBUH). Education from Islamic perspective is often defined by Muslim scholars from three different dimensions which are reflected in different concepts introduced, important among them are; tarbiyyah – the process of education that gives emphasis on physical and intellectual development of an individual; ta’dīb – the process of education that gives emphasis on nurturing good human beings with noble codes of conduct/ethics approved by Islam, so that he may conduct and position himself in society with justice; and taʿlīm – the process of education that is based on teaching and learning. The concept of education in Islam must take into consideration of all the dimensions stated above. No matter which one of the above concepts is preferable to scholars, it should not be used as a pretext for controversy and intellectual acrimony among scholars, because what does it matter is not the concept, but the practice, methodology and its objectives. Education occupies a significant position in Islamic civilization. The first revelation to Prophet Muḥammad (PBUH) in Sūrah al-‘Alaq (verses 1-4) is about the divine instruction to “reading by the name of God”, thus underscores the tawḥīd philosophy that education in its essence is not purely a mundane activity, but an integral part of faith. Recently, the concept of education in Islam has been influenced by secularism since the time of colonization and the collapse of the Ottoman Empire, which consequently resulted in the failure of the Muslim Ummah in its quest for nation building and development according to Islamic perspective. The purpose of education in Islam is to produce a good human being (al-insān al-ṣāliḥ), who is capable of delivering his/her duties as a servant of Allāh (ʿabdullāh) and His vicegerent (khalīfah) on earth. This paper is aimed at highlighting the main features of Islamic education, its methodology and objectives in comparison with the current system of education, which is predominantly secular in its philosophy and methodology. (Keywords: Education, secularism, philosophy)